1997
DOI: 10.1111/j.1949-8594.1997.tb17349.x
|View full text |Cite
|
Sign up to set email alerts
|

Science Attitudes of Selected Middle School Students in China: A Preliminary Investigation of Similarities and Differences as a Function of Gender

Abstract: Evaluating the attitudes of science students is important for teachers, curriculum developers, and those working with preservice teachers. Although in the United States a great deal of attitudinal research has been conducted with regard to science education, in the People's Republic of China very little work concerning science attitudes has been completed. This study will report on an evaluation of Chinese boys' and girls' attitudes toward selected science topics. Students attended a middle school in the city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
0
4
1
4
Order By: Relevance
“…A more current report by several authors (Jones, Howe, & Rua, 2000;Miller, Blessing, & Schwartz, 2006) also indicated that male students had a higher science attitude than females, even though there were also big gaps of in certain subjects, such as physics and biology. Contrasting results have also been found in several studies, indicating that female students had more positive attitudes or equal proportions of positive attitudes toward science as male students (Boone, 1997;Harwell, 2000;Murphy & Beggs, 2003;Said, Summers, Abd-El-Khalick, & Wang, 2016). According to Koballa and Glynn (2013), sociological reasons for gender inequality in science students might be the result of different cultural expectations of the genders by people close to the students (i.e., parents, peers, and teachers) and their experiences in science.…”
Section: Gender Issue In Science and Attitude Towards Sciencecontrasting
confidence: 60%
“…A more current report by several authors (Jones, Howe, & Rua, 2000;Miller, Blessing, & Schwartz, 2006) also indicated that male students had a higher science attitude than females, even though there were also big gaps of in certain subjects, such as physics and biology. Contrasting results have also been found in several studies, indicating that female students had more positive attitudes or equal proportions of positive attitudes toward science as male students (Boone, 1997;Harwell, 2000;Murphy & Beggs, 2003;Said, Summers, Abd-El-Khalick, & Wang, 2016). According to Koballa and Glynn (2013), sociological reasons for gender inequality in science students might be the result of different cultural expectations of the genders by people close to the students (i.e., parents, peers, and teachers) and their experiences in science.…”
Section: Gender Issue In Science and Attitude Towards Sciencecontrasting
confidence: 60%
“…These results concur with those from many studies, including Johnston et al (1999) who found that girls were significantly more positive than boys about doing science in the classroom, Woodward arid Woodward (1998) reported that girls showed a higher preference than boys for health education although the reverse was true for electricity. Boone (1997), who carried out a study in China, concluded that girls were more "pro-science" in their attitudes than boys. We feel that teachers need to be aware of, and cater for, gender differences in their science teaching.…”
Section: Gendermentioning
confidence: 96%
“…Araştırmacı, araştırmasında kız ve erkek öğrencilerin tümünün fenin zor olduğu yönünde benzer bir tutuma sahip olduğu sonucuna ulaşmıştır. Boone (1997) Çin'deki ortaokul öğrencilerinin Fen ve Teknoloji dersine yönelik tutumlarını cinsiyet faktörüne göre araştırmıştır. Araştırmacı çalışmasında, Çinli kız ve erkek öğrencilerin Fen ve Teknoloji dersine yönelik tutumlarını Fen ve Teknoloji konularını içeren likert tipinde ölçme aracı kullanarak belirlemiştir.…”
Section: İlgili Literatürunclassified